The structure of the 80S ribosome from Trypanosoma cruzi reveals unique rRNA components - Gao, Haixiao (2005)
We present analysis, by cryo-electron microscopy and single-particle reconstruction, of the structure of the 80S ribosome from Trypanosoma cruzi, the kinetoplastid protozoan pathogen that causes Chagas disease. The density map of the T. cruzi 80S ribosome shows the phylogenetically conserved eukaryotic rRNA core structure, together with distinctive structural features in both the small and large subunits. Remarkably, a previously undescribed helical structure appears in the small subunit in the vicinity of the mRNA exit channel. We propose that this rRNA structure likely participates in the recruitment of ribosome onto the 5′ end of mRNA, in facilitating and modulating the initiation of translation that is unique to the trypanosomes.